The influence of causal loop diagrams on systems thinking and information utilization in complex problem-solving - G.A. Veldhuis; E.M. Smits-Clijsen; R.P.M. van Waas; T. Hof; V. Maccatrozzo; E.A.J.A. Rouwette; J.H. Kerstholt (Computers in Human Behavior Reports)
Effective communication tools are essential for computer-aided approaches to policy analysis and design. The System Dynamics approach relies on model diagrams, such as Causal Loop Diagrams (CLDs), to communicate findings to clients. Despite their importance, there has been limited examination of the effectiveness of such diagrams in supporting professionals' reasoning about complex problems. In this study, we employed a mixed-method design with two sequential stimuli (CLD/Text or Text/CLD) to examine the impact of CLDs on professionals' (N = 14) ability to engage in systems thinking and information utilization. Through a case study on youth crime, utilizing a think-aloud method, we prompted police and municipal professionals to articulate their understanding of the problem's causes and the potential impact of an intervention. Additionally, we explored the influence of self-efficacy, response efficacy, and the need for cognition. Findings suggest that presenting a CLD following textual information enhances systems thinking and information utilization. We discuss implications and potential directions for future research.